Assessment of the Early Effects of 5,6-dimethylxanthenone-4-acetic acid using Macromolecular Contrast Media Enhanced Magnetic Resonance Imaging: Ectopic versus Orthotopic tumors - Seshadri, Mukund (2008)
PURPOSE: To investigate the early effects of a vascular disrupting agent (VDA) in ectopic and orthotopic tumors using macromolecular contrast media-enhanced magnetic resonance imaging (MMCM-MRI). METHODS AND MATERIALS: MMCM-MRI of ectopic and orthotopic MCA205 murine fibrosarcomas was performed using the intravascular contrast agent, albumin-(Gd-DTPA)(35). Change in longitudinal relaxation rate (ΔR1) was measured 24 hours after treatment with 5,6-dimethylxanthenone-4-acetic acid (DMXAA; 30 mg/kg) and used to compute tumor vascular volume and permeability. Correlative histology and immunohistochemistry was carried out along with measurement of tumor necrosis factor-alpha (TNF-α) and vascular endothelial growth factor (VEGF) levels in whole tumor extracts using the enzyme-linked immunosorbent assay (ELISA). RESULTS: Orthotopic tumors exhibited higher vascular volume (P<0.05) than ectopic tumors prior to treatment. Twenty-four hours after DMXAA treatment, a significant (P<0.0001) but differential reduction in ΔR1 (70% in ectopic and 50% in orthotopic tumors) was observed compared to baseline estimates. Consistent with this observation, higher levels of TNF-α, an important mediator of the antivascular activity of DMXAA were measured in ectopic tumors three hours post treatment compared to orthotopic tumors (P<0.05). Immunohistochemical (CD31) and histological (H&E) sections of ectopic and orthotopic tumors showed a highly tumor selective vascular damage following treatment with the presence of viable surrounding normal tissue. CONCLUSIONS: MMCM-MRI provided early quantitative estimates of change in tumor perfusion following VDA treatment that showed good correlation with cytokine induction. Differences in the response of ectopic and orthotopic tumors highlight the influence of host microenvironment in modulating the activity of VDAs.